Abbreviation as a Way of Coining Neologisms in Mass Media - Velykoroda, V.; Liabyga, N. (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The paper aims at analyzing abbreviation as one of the most productive ways of coining neologisms in mass media. The focus is made on the study of initial abbreviation and its subtypes; the authors discover several new ways of coining abbreviations. The analysis encompasses two major characteristics of abbreviations in mass media: their form and encoded meaning